A general source-sink model with inoperability constraints for robust energy sector planning - Tan, Raymond Girard R. (Animo Repository, 2011)
The concept of inoperability was originally introduced as a means of quantifying risk in systems comprised of interdependent subsystems, using a modified input-output framework. This paper describes a novel robust optimization model for energy planning with inoperability constraints. The formulation is based on the established source-sink framework, which has been used extensively for energy planning applications under various environmental footprint constraints. The proposed model determines the optimal allocation of various energy sources within a system to corresponding energy sinks or demands, while ensuring that inoperability limits of the latter are satisfied for multiple enumerated scenarios. The basic formulation results in a linear program (LP), while a mixed integer linear programming (MILP) extension is also described. In either case, a globally optimal solution can be easily determined if one exists. Illustrative case studies are then given to demonstrate this new method. © 2011.